Music of the shona people of Hwedza district - Matiure, Perminus (Midlands State University, 2020)
Music can be considered to be a product of a society's social and religious activities . It is apparent that every society has some form of sonic order which it calls music, however each society has its own ontology of music. What might be noise to one society may be music to the other .In other words, each society defines music within its confines of functionality...............................................